Chondroid Syringoma: A Rare Case Series of about Three Young Patients - Nechal Kaur; Neelam Gupta; Vikas Dubey; Neetu Bala (New Advances in Medicine and Medical Science Vol. 6, 2023)
This study highlights a rare case series of chondroid syringoma in three young patients. Chondroid syringoma is also known as mixed tumour of the skin. It is an uncommon, biphasic cutaneous neoplasm that resembles a salivary gland pleomorphic adenoma. Because it is so uncommon, many cases are initially misdiagnosed as cysts or other cutaneous adnexal neoplasms, and are frequently only discovered after being sent for histopathological testing. The tumour is composed of a proliferation of epithelial cells present in a myxoid and chondroid matrix. Although chondroid syringoma was predominantly benign, sweat-gland tumour, the usual presentation is of an asymptomatic, slowly growing mass, typically located on the head and neck region. Although it usually presents in middle and older aged patients, we are presenting three younger patients with Chondroid syringoma, located over the back, nose and cheek, respectively. It is difficult to diagnose chondroid syringoma clinically or radiologically. All of our cases were misdiagnosed. Excisional biopsy with histopathological examination and histochemical stains remains the gold standard.